Limiting factorials

Calculus Level 4

lim n ( ( 5 n 3 n ) ( 3 n 2 n ) ) 1 / n = a a b 2 b \large \lim_{ n \to\infty }{ \left( \frac{ 5n \choose 3n }{ 3n \choose 2n } \right) }^{1/n} =\frac{ { a }^{ a } }{ { b }^{ 2b } }

The equation above holds true for positive integers a a and b b . Find the value of a + b a+b .


Bonus: Do it without Stirling's approximation .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Rishi Sharma
Feb 4, 2017

Let P = lim n ( ( 5 n 3 n ) ( 3 n 2 n ) ) 1 n \displaystyle P =\lim_{ n \rightarrow \infty }{ \left( \dfrac{ 5n \choose 3n }{ 3n \choose 2n } \right) }^{ \small \dfrac{1}{n} } We notice that ( 5 n 3 n ) ( 3 n 2 n ) = r = 0 2 n 1 5 n r 3 n r \displaystyle \dfrac{ 5n \choose 3n }{ 3n \choose 2n } = \prod_{ r=0 }^{ 2n-1 }\dfrac{ 5n-r }{ 3n-r } .So P = lim n ( r = 0 2 n 1 5 n r 3 n r ) 1 n \displaystyle P = \lim_{ n \rightarrow \infty }{ \left( \prod_{ r=0 }^{ 2n-1 }\dfrac{ 5n-r }{ 3n-r } \right) }^{ \dfrac{1}{n} } . Now taking log on both sides. log P = lim n 1 n log r = 0 2 n 1 5 n r 3 n r \displaystyle \log {P} = \lim_{ n \rightarrow \infty } \dfrac{ 1 }{ n } \log \prod_{ r=0 }^{ 2n-1 }\dfrac{ 5n-r }{ 3n-r } Using log a b = log a + log b \log ab = \log a +\log b . We get log P = lim n 1 n r = 0 2 n 1 log ( 5 n r 3 n r ) log P = 0 2 log ( 5 x 3 x ) d x \displaystyle \log P = \lim_{ n \rightarrow \infty } \dfrac{ 1 }{ n }\sum_{ r=0 }^{ 2n-1 }\log{ \left( \dfrac{ 5n-r }{ 3n-r } \right) } \rightarrow \log P = \int_0^2 \log{ \left( \dfrac{ 5-x }{ 3-x } \right) }dx

Hence we get P = 5 5 3 6 \displaystyle P = \dfrac{ { 5 }^{ 5 } }{ { 3 }^{ 6 } }

So a = 5 a=5 & b = 3 b=3 . Hence a + b = 8 \boxed {\boxed{ a+b=8}}

Truly amazing question to do without stirling approximation Did the same :-D

Ayush Sharma - 3 years, 12 months ago
Aareyan Manzoor
Jun 10, 2017

alternatively write L = lim n ( Γ ( 5 n + 1 ) Γ ( n + 1 ) Γ 2 ( 3 n + 1 ) ) 1 / n L=\lim_{n\to \infty} \left( \dfrac{\Gamma(5n+1)\Gamma(n+1)}{\Gamma^2(3n+1)} \right)^{1/n} we use: ln ( L ) = lim n ( ln ( Γ ( 5 n + 1 ) ) 2 ln ( Γ ( 3 n + 1 ) ) + ln ( Γ ( n + 1 ) ) n ) = l o p i t a l lim n 5 ψ ( 5 n + 1 ) 6 ψ ( 3 n + 1 ) + ψ ( n + 1 ) \ln(L)=\lim_{n\to \infty}\left(\dfrac{\ln(\Gamma(5n+1))-2\ln(\Gamma(3n+1))+\ln(\Gamma(n+1))}{n}\right)=^{l'opital} \lim_{n\to \infty} 5\psi(5n+1)-6\psi(3n+1)+\psi(n+1) we use tha fact as asymptopic levels ψ ( n + 1 ) = γ + H n ln ( n ) \psi(n+1)=-\gamma+H_n\approx \ln(n) ln ( L ) = lim n 5 ln ( 5 n ) 6 ln ( 3 n ) + ln ( n ) L = 5 5 3 6 \ln(L)= \lim_{n\to \infty} 5\ln(5n)-6\ln(3n)+\ln(n)\to L=\dfrac{5^5}{3^6}

Guilherme Niedu
Jun 20, 2017

L = lim n [ ( 5 n 3 n ) ( 3 n 2 n ) ] 1 / n \large \displaystyle L = \lim_{n \rightarrow \infty} \left[ \frac{5n \choose 3n }{3n \choose 2n } \right ] ^{1/n}

L = lim n [ ( 5 n ) ! ( 3 n ) ! ( 2 n ) ! ( 2 n ) ! n ! ( 3 n ) ! ] 1 / n \large \displaystyle L = \lim_{n \rightarrow \infty} \left[ \frac{(5n)!}{(3n)! (2n)!} \cdot \frac{(2n)! n!}{(3n)!}\right ] ^{1/n}

L = lim n [ ( 5 n ) ! n ! ( 3 n ) ! ( 3 n ) ! ] 1 / n \large \displaystyle L = \lim_{n \rightarrow \infty} \left[ \frac{(5n)! n!}{(3n)! (3n)!}\right ] ^{1/n}

By Stirling's approximation :

L = lim n [ 10 π n ( 5 n / e ) 5 n 2 π n ( n / e ) n 6 π n ( 3 n / e ) 3 n 6 π n ( 3 n / e ) 3 n ] 1 / n \large \displaystyle L = \lim_{n \rightarrow \infty} \left[ \frac{\sqrt{10 \pi n } (5n/e)^{5n} \cdot \sqrt{2 \pi n } (n/e)^{n}}{\sqrt{6 \pi n } (3n/e)^{3n} \cdot \sqrt{6 \pi n } (3n/e)^{3n}} \right ] ^{1/n}

L = lim n [ 20 36 5 5 n 3 6 n ] 1 / n \large \displaystyle L = \lim_{n \rightarrow \infty} \left[ \sqrt{\frac{20}{36}} \cdot \frac{5^{5n}}{3^{6n}} \right] ^{1/n}

L = lim n [ 20 36 ] 1 / n lim n [ 5 5 n 3 6 n ] 1 / n \large \displaystyle L = \lim_{n \rightarrow \infty} \left[ \sqrt{\frac{20}{36}} \right]^{1/n} \cdot \lim_{n \rightarrow \infty} \left [ \frac{5^{5n}}{3^{6n}} \right] ^{1/n}

L = 5 5 3 2 3 \color{#20A900} \boxed{ \large \displaystyle L = \frac{5^5}{3^{2 \cdot 3}} }

Thus:

a = 5 , b = 3 , a + b = 8 \color{#3D99F6} \large \displaystyle a=5, b=3, \boxed{\large \displaystyle a+b=8 }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...